2021
DOI: 10.3947/ic.2020.0109
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Mavrilimumab in Viral Infections Including SARS-CoV-2 Infection - A Brief Review

Abstract: Hyperinflammation and cytokine storm has been noted as a poor prognostic factor in patients with severe pneumonia related to coronavirus disease 2019 (COVID-19). In COVID-19, pathogenic myeloid cell overactivation is found to be a vital mediator of damage to tissues, hypercoagulability, and the cytokine storm. These cytokines unselectively infiltrate various tissues, such as the lungs and heart, and nervous system. This cytokine storm can hence cause multi-organ dysfunction and life-threatening complications. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This finding was contrary to previous studies which have suggested that some antiviral drugs (hydrocortisone, mavrilimumab, etc) were associated with decreased ACM in patients with COVID-19. [ 29 , 32 , 89 , 90 ] It is difficult to explain this result, but it might be related to the difference of participants’ selection in differential studies. For instance, the findings of this NMA were based on a larger sample size (i.e., more participants were included).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding was contrary to previous studies which have suggested that some antiviral drugs (hydrocortisone, mavrilimumab, etc) were associated with decreased ACM in patients with COVID-19. [ 29 , 32 , 89 , 90 ] It is difficult to explain this result, but it might be related to the difference of participants’ selection in differential studies. For instance, the findings of this NMA were based on a larger sample size (i.e., more participants were included).…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, most of the previous studies presented a smaller sample size. [ 29 , 32 ] The present study differed from earlier studies, [ 90 , 91 ] which selected subjects with all infection levels (i.e., mild, moderate and severe infections). Furthermore, prior studies were inadequate for the analyses stratified by different infection levels (i.e., non-severe and severe infection) in medications of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation